Typification of the name Asperula rupestris (Rubiaceae) - Di Gristina, Emilio; Scafidi, Filippo; Domina, Gianniantonio (Phytotaxa, 2021)
Asperula rupestris Tineo (1827: 276) is a species endemic to Sicily, southern Italy. It is a chasmophyte growing on north-exposed calcareous rocks and cliffs of the main promontories of NW Sicily and the islands of Favignana and Marettimo, Egadi Islands, NW of Siciliy (see e.g., Giardina et al. 2007).